Theoretical studies of the rotational and tautomeric states, electronic and spectroscopic properties of favipiravir and its structural analogues: a potential drug for the treatment of COVID-19. Issue 1 (1st January 2020) - Umar, Yunusa
ABSTRACT: Favipiravir is a broad spectrum antiviral drug that has shown activity against many viruses. Sequel to the recent outbreak of COVID-19, favipiravir is investigated as one of the potential drugs for the treatment of SARS-CoV-2. To augment these efforts, this article reports the rotational isomers, tautomeric states, electronic and spectral properties of favipiravir and its five analogues (Cl, Br, H, CN and CH3 ) using quantum chemcial code. The enol forms are more stable and the calculated keto–enol relative energies are in the range of 7.86–10.72 kcal/mol in the gas phase and 1.07–3.46 kcal/mol in the solution phase. The relative stabilization of the more polar keto structure in water environment leads to a significant reduction in keto–enol relative energy by 68% for T705, 71% for T705–Cl and T705–Br, 86% for T1105 (H), 88% for T705–CN and 80% for T705–CH3 . The density functional theory and time-dependent density functional theory with the 6-311++G(d, p) basis set were used in the computation. The theoretical results were successfully compared with available experimental and theoretical data.